Introducing a software-based method to assess and manipulate visual attention : feasibility and initial validation - Samson, Lelia (2015)
A new software-based method to assess and manipulate visual attention (VA) is introduced. The method uses circular, transparent outlines (‘bubbles’) that move over visual stimuli. To evaluate the method’s feasibility and validity, 50 men watched same- and opposite-sex erotica in self-directed and manipulated VA conditions while their psychophysiological responses were recorded. Participants were instructed to select a bubble by using a computer-mouse which kept selected content visible while darkening the rest of the screen. Only one bubble was available during the manipulated VA conditions. Findings revealed that participants could successfully perform the experimental task and that their spontaneous VA was consistent with predictions. Furthermore, the method successfully manipulated VA. The benefits of this application include the ability to measure and direct VA in multiple participants simultaneously, its ease of use, as well as its provision of relatively noise-free data. Advantages of using this method in social/behavioral science research are discussed.